2000
DOI: 10.1089/088922200309304
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1-Induced Inhibition of CD45 Tyrosine Phosphatase Activity Correlates with Disease Progression and Apoptosis, but Not with Anti-CD3-Induced T Cell Proliferation

Abstract: The tyrosine phosphatase CD45 is a key positive element in multiple lymphocyte signaling pathways. To understand the contribution of CD45 to HIV-1-induced T cell hyporesponsiveness and apoptosis we evaluated the CD45-associated tyrosine phosphatase activity of lymphocytes from patients with different stages of HIV-1 disease and compared it with CD45 expression, spontaneous and Fas-induced apoptosis, anti-CD3-induced T cell proliferation, distribution of CCR5 delta32/wt, and cytokine production. The proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The authors suggested that CD3 and CD4 signaling could induce an impaired proliferative response to antigen, anergy and apoptosis induction. The impairment of CD45 tyrosine phosphatase activity correlates with disease progression and the level of T cell apoptosis [121]. Many viral proteins like Tat, Vpr, Nef, gp120 have apoptotic properties [122,123].…”
Section: Role Of Cd45 In Hiv-1 Mediated Apoptosismentioning
confidence: 99%
“…The authors suggested that CD3 and CD4 signaling could induce an impaired proliferative response to antigen, anergy and apoptosis induction. The impairment of CD45 tyrosine phosphatase activity correlates with disease progression and the level of T cell apoptosis [121]. Many viral proteins like Tat, Vpr, Nef, gp120 have apoptotic properties [122,123].…”
Section: Role Of Cd45 In Hiv-1 Mediated Apoptosismentioning
confidence: 99%
“…The protein tyrosine kinases (PTKs), Lck, Fyn, and ZAP‐70, were significantly decreased in T cells from HIV‐1‐positive subjects, and these alterations affected selectively T cells of HIV‐1‐infected patients since B cell PTKs, Syk and Lyn, were detected structurally and functionally intact 6 . Furthermore, CD45, a key positive phosphatase in multiple lymphocyte signaling pathways, is affected 8 . Impairment of CD45 activity correlates with disease progression and with levels of T cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, CD45, a key positive phosphatase in multiple lymphocyte signaling pathways, is affected. 8 Impairment of CD45 activity correlates with disease progression and with levels of T cell apoptosis. Altogether, these alterations may underlie the HIV-induced impairment of lymphocyte functions and may potentially predict disease progression.…”
Section: Introductionmentioning
confidence: 99%